The Synthesis and Characterisation of Fused Aromatic Hydrocarbons and Their Material and Ligand Applications - LARKIN, EUGENE JAMES (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2019)
This thesis details the synthesis of various extended, aromatic ligands and investigates their behaviour in a number of different applications. The work carried out represents a contribution to the understanding of the properties of compounds with potential applications in future electronic devices, such as semiconductors and emissive materials. A literature review of the emerging strategies for the production of graphene nanoribbons (GNRs) is given, followed by the synthesis of several nitrogen-containing precursors. These precursors are then deposited on Au(111) and their ability to form polymeric structures is examined using STM and AFM. In the case of a novel triphenylene-based precursor, short nitrogen-containing GNRs are obtained. The synthesis and characterisation of novel platinum acetylides, bearing highly-conjugated hexa-peri-hexabenzocoronene (HBC) cores is also discussed. The photophysical properties of these complexes, which displayed a broad phosphorescent emission profile at room-temperature, are described in detail. The synthesis of these complexes has given further insight into the behaviour of organometallic complexes of HBC, of which there are relatively few reports. Further work on a family of platinum acetylides with extended aromatic diimine ligands based upon 1,10-phenanthroline is also discussed. This work revealed the effect on the photophysical properties of the incorporation of ligands with low-lying acceptor orbitals in such complexes. A description of the synthesis of novel bis-cyclometalated Ir(III) complexes with a highly conjugated, partially-fused ligand is also provided. The characterisation and optical behaviour of these complexes is discussed in detail.
APPROVED
Keywords: Inorganic Materials Chemistry, On-surface synthesis, Platinum(II) acetylides, Ir(III) complexes